Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.15406/smdij.2017.01.00012
|View full text |Cite
|
Sign up to set email alerts
|

Depression, obstructive sleep apnea and psychosocial health

Abstract: Depression and Obstructive sleep apnea (OSA) are the major associated comorbidities. OSA is a rapidly growing problem in the society that is connected to the rising rates of obesity; at the same time, the depression rate is also increasing day by day. Patients with OSA present with sleep problems, anxiety, and depressive symptoms, depressive patients can also present with the same symptoms. The quality of an individual's health can be improved by the early detection of the symptoms of overlapping OSA and depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 91 publications
0
1
0
Order By: Relevance
“…DOCA has been linked to a decline in QOL in the general population [23,24]. The stroke-specific QOL scale (SS-QOL) evaluates various aspects such as energy levels, engagement in family activities and social roles, speech or language impairment, mobility and functioning, mood and personality, self-care ability, and changes in vision, cognition, and productivity [23].…”
Section: Discussionmentioning
confidence: 99%
“…DOCA has been linked to a decline in QOL in the general population [23,24]. The stroke-specific QOL scale (SS-QOL) evaluates various aspects such as energy levels, engagement in family activities and social roles, speech or language impairment, mobility and functioning, mood and personality, self-care ability, and changes in vision, cognition, and productivity [23].…”
Section: Discussionmentioning
confidence: 99%
“…These are important risk factors that should be considered in propensity score matching while building cohorts. The authors noted that all cohorts were matched for age, sex, and co-morbidities, but the large difference in co-morbidities in the CPAP group indicated that these patients likely had other co-morbidities and behavioral factors that were not considered [ 6 ]. While authors matched for many relevant comorbidities, the results may still be biased due to the nature of the retrospective study.…”
Section: Selection Biasmentioning
confidence: 99%
“…Patients with OSA have a higher prevalence of depression [12,65]. These depressive symptoms may gradually improve with CPAP treatment [66,67].…”
Section: Depressionmentioning
confidence: 99%